Conceptualising mental distress from an African psychology paradigm: using an interpretative phenomenological analysis of the views of traditional healers - Nabo-Bazana, Sandisiwe Sifanelwe (Rhodes University, Faculty of Humanities, Department of Psychology)
With South Africa's long history of colonialism and racial oppression, there are still services in the country that many South Africans cannot relate to, including psychology. Research shows that many South Africans experience and are affected by mental distress due to several factors, including poverty, unemployment, and traumatic experiences. Managing and treating such distress has always been challenging for most South Africans. Some debates question the relevance of psychological services from the West in a South African context. This study explores other approaches to psychology that look beyond the Biopsychosocial model when dealing with certain types of disorders in an African context. African psychology, or the Afrocentric approach, looks at what is beneath the surface, not just the presenting problem. Mainstream psychology strives to be universal and applicable to all. However, African psychology disagrees with this notion. African psychology perceives human beings as strongly influenced by social and cultural influences. The focus of this approach includes the spiritual realm and the attached meanings. There is evidence for the need to merge Traditional and Western medicine. The research methodology for this study is qualitative, using Interpretative Phenomenological Analysis. IPA allows for a critical engagement with the ways in which participants construct their reality. The researcher carried out semi-structured interviews to enable participants, all traditional healers (3 female and 2 male), to narrate their experiences dealing with mentally distressed clients. The accounts of these traditional healers were analysed focusing on people who have experienced mental distress. From the analysis and synthesis of the themes, findings illustrate how traditional healers conceptualise and construct mental distress from an African Psychology paradigm. An emerging core theme was the importance of the divine call and its influence on the chosen treatments. More studies are needed to illustrate the potential for collaboration between African Traditional healing and EuroAmerican healing practices, to provide holistic services to people in need.
Keywords: Healers -- South Africa; Traditional healer; Mental distress; Black psychology; Afrocentrism